A subject’s autonomy: Undidactic mediation in Georg Lukács and John Dewey - Baldacchino, John (Policy Futures in Education, 2023)
This paper looks at autonomy through the dynamic relationship between particularity, experience, and subjectivism in the works of Georg Lukács and John Dewey. While the focus on autonomy appears to be initially focused on the relationship between universality and particularity, the ultimate goal is to then situate the discussion on the horizon of education. Given Dewey’s and Lukács’s common Hegelian lineage, this paper looks at whether they retain elements of commonality, especially in terms of the arts, and whether forms of mediation in art and education could avoid becoming didactic. To explore these questions, this paper revisits subjectivity in two forms: (a) as a form of mediation, and (b) as immediate experience. Some play on the subject as being (qua subjectivity) and a subject (like art) in the curriculum might enter the discussion. However, the former sense of subject tends to be more central than the latter. While immediate subjectivity is critiqued by Lukács as being open to a fragmentation of reality that leads to forms of oppression, the Deweyan perspective proposes a way out of the cycle that traps subjectivism between didactic and fragmentary forms of being. Can the subject mediate without proposing a form of learning that presumes reality as a fixed ground? And could we predicate subjectivist immediacy by what Dewey, in Experience and Nature calls “the recognition of ‘subjects’ as centres of experience” that are, in effect, “equivalent to the emergence of agencies equipped with special powers of observation and experiment”? The binding horizon for both questions will be that of what Lukács calls the speciality of the artwork’s own “world” [eigenen “Welt”] and the dilemmas that this could raise when contextualized in education.